Em um rabo de foguete: Ferreira Gullar e a crítica as culturas políticas das esquerdas (1970-1985) - Oliveira, Marcus Vinícius Furtado da Silva [UNESP] (2015)
This work aims to comprehend how the experiences with the exile and latin american dictatorships are configured as traumatic events capable of alter deeply the world conceptions of the poet and critic Ferreira Gullar, between 1963 and 1985. For this, we will use as historical sources some essays written by the poet along that period, as his memory book published in 1998. In the analyzes of these essays, we pretend to demonstrate that, during the 1960's, Gullar initiates a construction process of a world conception, close to the communist political culture, held by the PCB. In the exile experiences this world conception is altered, so that the revolutionaries expectations are canceled in Gullar. It occurs due to this experiences has been configured as traumas. The trauma, in this sense, is comprehended as a past that becomes present, being capable of transforming the readings that the traumatized subject operates about his reality and his own past. Therefore, the crises of the revolutionary expectation, as the adoption of a reformist political culture occurs, in Gullar, due to the traumas originated by the exile and the dictatorships